Collision or Collaboration : Archaeology Encounters Economic Development - Gould, Peter G.; Pyburn, K. Anne (One World Archaeology, 2017)
Archaeology has an often contentious relationship with the consequences of economic development. Tourism, urban development and natural resource exploitation have generated adverse impact on the archaeological record, indigenous cultures and local communities worldwide. Over the decades, international conventions, national laws and corporate ventures have sought to address the problems, but too often they have fallen short and immense challenges remain. Looking ahead, the contributions to this volume constitute a global conversation on the most salient issue facing archaeology as it interacts with economic development: Is collision with development still the best course? Or, is a more effective strategy to pursue collaborative relationships with the forces of economic and social change? .